Characterization of Lactobacillus plantarum strains isolated from Turkish pastırma and possibility to use of food industry - DINCER,Emine (2020)
Abstract Five Lactobacillus plantarum strains (which were previously isolated from Turkish pastırma), were evaluated for the possibilities of using in the food industry. Antimicrobial properties, metabolic activities, exopolysaccharide production and antibiotic resistance were investigated. It was also assessed probiotics features such as adhesion ability, survival in simulated gastric environment and acid tolerance analysis. Antimicrobial activity was characterized based on effects of several enzymes, different temperature and pH. All strains showed remarkable antimicrobial activity and antimicrobial substances were found resistant to enzymes, high temperature and low pH. Metabolic activities and exopolysaccharide production of the strains were found relatively weak. Determinate to antibiotic susceptibility patterns 14 different antibiotics used and strains were found reliable in terms of transferable resistance genes except for erythromycin. All strains showed resistance to acidic condition and gastric environment. However, adhesion ability of strains was found relatively low. All findings showed that, these strains potential candidate for use in food industry especially as natural food preservatives because of antimicrobial activity capacity and one strain (S2) have remarkable potential to use as starter cultures or probiotics.